THE FEATURES OF TRAINING OF TEACHERS AND STUDENTS TO THE USE OF INFORMATION TECHNOLOGIES TRAINING OF MATHEMATICS IN HIGHER EDUCATIONAL ESTABLISHMENTS (Journal of Information Technologies in Education (ITE), 2012)
The article deals with the current issues to improve the educational process at higher school on the basis of introduction of information and communication technologies training. The main attention was paid to the problem of determining the conditions, psychological and pedagogical features of application of existing pedagogical software systems for teaching mathematics in higher educational establishments. Teachers’ and students’ appropriate training to the use of information technologies training should be considered one of the conditions for increasing of efficiency of the process of informatization of education.
Keywords: computer training for teachers and students; information and communication technologies; information culture; information technologies; information technologies training; informatization of education